Mechanistic discoveries and simulation‐guided assay optimization of portable hormone biosensors with cell‐free protein synthesis. Issue 2 (30th November 2021) - Hunt, John Porter; Galiardi, Jackelyn; Free, Tyler J.; Yang, Seung Ook; Poole, Daniel; Zhao, Emily Long; Andersen, Joshua L.; Wood, David W.; Bundy, Bradley C.
Abstract: Nuclear receptors (NRs) influence nearly every system of the body and our lives depend on correct NR signaling. Thus, a key environmental and pharmaceutical quest is to identify and detect chemicals which interact with nuclear hormone receptors, including endocrine disrupting chemicals (EDCs), therapeutic receptor modulators, and natural hormones. Previously reported biosensors of nuclear hormone receptor ligands facilitated rapid detection of NR ligands using cell‐free protein synthesis (CFPS). In this work, the advantages of CFPS are further leveraged and combined with kinetic analysis, autoradiography, and western blot to elucidate the molecular mechanism of this biosensor. Additionally, mathematical simulations of enzyme kinetics are used to optimize the biosensor assay, ultimately lengthening its readable window by five‐fold and improving sensor signal strength by two‐fold. This approach enabled the creation of an on‐demand thyroid hormone biosensor with an observable color‐change readout. This mathematical and experimental approach provides insight for engineering rapid and field‐deployable CFPS biosensors and promises to improve methods for detecting natural hormones, therapeutic receptor modulators, and EDCs. Graphical Abstract and Lay Summary: Compounds that interact with nuclear hormone receptor signaling can directly influence health outcomes, motivating efforts to develop a low‐cost cell‐free hormone biosensor for screening applications. In this study, the authors seek to elucidate the molecular mechanism of a hormone biosensor, enabling simulation‐guided sensor optimization which is confirmed experimentally. The described on‐demand test is an important step toward rapid and field‐deployable hormone biosensors, and the assay optimization principles may be usefully generalized to other biosensors that employ substrate conversion reactions.